The Influence of Customer Service Quality on the Satisfaction Level of PT Angkasa Pura II Service Users at Supadio Pontianak International Airport - Utin Shabrina Nur Amalia; Yunus Purnama (CV. Rayyan Dwi Bharata, 2023)
Service quality and service user satisfaction are two different but closely related concepts. This study aims to determine the effect of customer service quality on the satisfaction level of service users of PT. Angkasa Pura II at Supadio International Airport Pontianak. This study uses quantitative data. There are 2 sources of data used, namely primary data and secondary data. This research was conducted by distributing questionnaires by collecting a sample of 100 respondents. Based on the results of the research that has been discussed, the quality of customer service on the satisfaction level of service users has an influence with a significance value of 0.000 0.05 with a t-count value of 19.973 t-table 0.196 and the test results for the coefficient of determination is 0.803 or 80.3% and the remaining 19.7% is influenced by other factors outside of this study.